“The artist has to make a long journey through the demands of painting:” A reading of the exhibition “Exceptions: Aspects of Expressionism in Greece”, Athens (June 2019 to August 2020). - Foukaneli, Georgia (The Historical Review/La Revue Historique, 2022)
A reading of the exhibition “Exceptions: Aspects of Expressionism in Greece”, Athens (June 2019 to August 2020).